Effect of supine posture on peak expiratory flow rates in asthma. - Haffejee, I E (1988)
In order to determine the effect of supine posture alone on the peak expiratory flow rate (PEFR) in children with asthma, 22 children with asthma of varying severity had PEFR readings taken in the standing position and subsequently at 30 minute intervals in the supine position for a period of up to four hours. In order to minimise any stress factors no other procedures--for example, taking of blood specimens--were performed during the duration of the tests, which were carried out in a relatively dust free room with no curtains and minimal furniture. Fifteen non-asthmatic children acted as controls. The results showed a significant drop in the PEFR readings in the supine position in asthmatic children compared with the controls; this reverted back to baseline levels on assuming an upright posture at the end of the test without any medication. It is concluded that airflow obstruction can be induced by supine posture per se in asthmatic children; this may be a major factor contributing to nocturnal wheeze or cough.